Peroxisome Proliferator-Activated Receptor-γ Is Critical to Cardiac Fibrosis - Huang-Jun Liu; Hai-Han Liao; Zheng Yang; Qi-Zhu Tang (PPAR Research)
Peroxisome proliferator-activated receptor-γ (PPARγ) is a ligand-activated transcription factor belonging to the nuclear receptor superfamily, which plays a central role in regulating lipid and glucose metabolism. However, accumulating evidence demonstrates that PPARγ agonists have potential to reduce inflammation, influence the balance of immune cells, suppress oxidative stress, and improve endothelial function, which are all involved in the cellular and molecular mechanisms of cardiac fibrosis. Thus, in this review we discuss the role of PPARγ in various cardiovascular conditions associated with cardiac fibrosis, including diabetes mellitus, hypertension, myocardial infarction, heart failure, ischemia/reperfusion injury, atrial fibrillation, and several other cardiovascular disease (CVD) conditions, and summarize the developmental status of PPARγ agonists for the clinical management of CVD.